KOMPOSISI DAN STRUKTUR VEGETASI DASAR PADA LOKASI BEKAS PENAMBANGAN EMAS DI NAGARI GUNUNG MEDAN KECAMATAN SITIUNG KABUPATEN DHARMASRAYA - Astuti, Lici - (Pendidikan Biologi, 2014)
Gold mining activities causing disturbance and vegetation succession in the used mine location, so that research on the composition and structure of vegetation Basic On used mine Location in Gunung Medan area of Sitiung district Dharmasraya regency, with the aim to know the basic composition of the vegetation consist of type and quantity, structure vegetation cover density (K), relative density (KR), frequency (F), relative frequency (FR), diversity index (H1) and the factor of chemical physics at the used mine location. Descriptive survey research methods in September 2014. Samples of soil and vegetation samples basis taken of four research stations is the used mine location after 1 year (station I), 2 years (station II), 3 years (station III), 4 years (station IV ). Analysis of soil in the laboratory Botany Biology Study Program STKIP PGRI West Sumatra. Identify basic vegetation at Andalas University Herbarium (ANDA). The composition of the base vegetation is 616 people, 11 families, 19 species. The highest KR Borreria alata (Aubl.) DC. 67.198%. The highest FR Brachiaria eruciformis (Sm.) Griseb 20.008%. The highest H1 Scleria sumatrensis Retz. and Borreria alata (Aubl.) DC. 1.398. 330C-360C air temperature, soil temperature of 280C-310C, humidity 34%-40%, soil pH from 6.5 to 7.1 and the highest soil water content 21.867%.